What Makes Them Happy?: Measuring the happiness of Certified Public Accountants through the COVID-19 Pandemic in Cotabato Province, Philippines - Christian Eligius A. Jimenez; Jay-R G. Vildac; Zosimo O. Membrebe Jr. (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
Since the onset of the COVID-19 pandemic, governments across the world have enforced lockdown measures to limit the transmission of the virus. Although these restrictions have been effective in reducing physical health risks, they have also raised concerns about their negative impact on individuals’ well-being, particularly in terms of life satisfaction and happiness. This paper analyzes the feeling of happiness of the Certified Public Accountants in the Cotabato Province and measures their satisfaction with the 10 happiness domains, to aid the limited understanding of how an outbreak can affect people’s well-being. The central idea is to assess the overall happiness of the respondents, investigate the relation of happiness and 10 domains, and to identify which of these domains affect their happiness. Pearson correlation coefficient (r) was used to examine the relationship between happiness and the ten happiness domains. Multiple regression was used to identify the domains that significantly predicted happiness. Results showed that all ten domains were significantly and positively correlated with happiness. The final regression model identified health, environment, time balance, governance, and psychological well-being as significant predictors of happiness.